Produto à base de própolis (LLOS) na dieta de bovinos inteiros confinados : comportamento animal, respostas fisiológicas e sanguíneas - Faria, Leonardo Avanzzi Nunes (2010)
The purpose of this work was to evaluate the animal behavior and the physiological and blood responses of confined animals to a diet with different concentrations of LLOS, a propolis-based product. This experiment was conducted at the Sector of Beef Bovine Culture of the Experimental Farm of Iguatemi (FEI) of the State University of Maringá, from April 19th to July 27th, 2007. The experimental ration was formulated according to the recommendations of the NRC (2006), containing 70.2% TDN and 13.5% CP. The treatments were: control (CON) and addition of two propolis-based products (LLOS) at different propolis concentrations (LLOSC1 and LLOSC1+). The feeding of the animals was divided into two meals, the first being supplied at 8 a.m. and the second at 4 p.m., the volume and the concentrate being mixed in the trough. All the animals were fed the same experimental ration (Table 1); however, the propolis-based products were added to the ration when it was delivered to the animals. The ration was composed of 50% volume and 50% concentrate, composed of corn silage and commercial concentrate. Twenty-four male bulls (European X Zebu), with no defined relatedness, mean live weight of 320.69 ± 27.89 kg and approximate age of 24 months were used. The following measurements of behavior were made: eating (COM), drinking (BEB), walking (AND), ruminating while standing (RUP), ruminating while lying down (RUD), standing (EP) and lying down (DET). These observations were made each 15 days during 24 hours, at 15 min intervals, on the same days of the evaluations of the climatic changes, totalizing three observations during the experimental period. The behavioral data were distributed in four periods of 6 hr: period 1 (7 a.m. to 12 p.m.), period 2 (1 to 6 p.m.), period 3 (7 p.m. to 12 a.m.) and period 4 (1 to 6 a.m.). It was observed that the animals spent more time at the trough and drinker and ruminating while standing during periods 1 and 2, when compared to periods 3 and 4. On the other hand, the activities COM and RUEMP were equal in periods 3 and 4, while BEB was different, with the animals going less to the drinker during the early morning. When the AND and EMP behaviors were analyzed, it was noticed the influence of the periods and sides of the confinement (P<0.05). The animals on Side 1 of the feddlot spent more time in AND in periods 1, 3 and 4, and less time in AND in period 2, than those on Side 2. When the sides of the feddlot were analyzed, more animals of Side 1 showed behavior AND in period 1, followed by periods 3, 4 and 2. For the side 2 of the feddlot, the responses decreased from period 2 to periods 4, 1 and 3. For the EMP behavior, the animals of side 1 showed it more in periods 1 and 2, while those animals of side 2 showed it more in periods 3 and 4. The animals of Side 1 spent more time in EMP behavior during period 2, followed by periods 1,3 and 4.The treatments did not significantly influence the blood variables cortisol, glucose and urea (P>0.05).With the help of an hemogram, it was observed that erythrocytes, hemoglobin, hematocrit, VCM, HCM and CHCM did not show significant differences (P>0.05); however, the leukocytes and their varieties showed consistent differences, with greater amounts or concentrations of white blood cells in the LLOSC1+ treatment and lower ones in the CON treatment. The results of our work showed that the supply of propolis-based diet did not bring positive evidence for its use. On the other hand, the layout of the confinement facility may bring great economic and animal welfare improvements.